Tremella ananatis sp. nov. and Tremella lamprococci sp. nov., two yeast species associated with bromeliads. Issue 2 (28th February 2022) - Navarro, Hector M. C.; Félix, Ciro Ramon; Tavares, Victor D. F. S.; de Sousa, Francisca M. P.; Santos, Ana R. O.; Morais, Paula B.; Rosa, Carlos A.; Valente, Patricia; Landell, Melissa Fontes
Abstract : Eight yeast isolates with an affinity to the genus Tremella were obtained from bromeliads from different locations in Brazil. Although the formation of basidia and basidiocarp were not observed, on the basis of the results of sequence analysis of the D1/D2 domain of the large subunit (LSU) rRNA gene and internal transcribed spacer (ITS) region, we suggest that these isolates represent two novel species of the genus Tremella . These yeasts are phylogenetically related to Tremella saccharicola and Tremella globispora . Therefore, we propose Tremella ananatis sp. nov. and Tremella lamprococci sp. nov. as novel yeast species of the order Tremellales (Agaricomycotina, Basidiomycota). Sequence analysis revealed that Tremella ananatis sp. nov. differs by 11 and 28 nucleotide substitutions from Tremella saccharicola in the D1/D2 sequence and ITS region, respectively. Moreover, Tremella lamprococci sp. nov. differs by 15 and 29 nucleotide substitutions from Tremella globispora in the D1/D2 sequence and ITS region, respectively. The holotypes of Tremella ananatis sp. nov. and Tremella lamprococci sp. nov. are CBS 14568 T and CBS 14567 T, and the MycoBank numbers are MB840480 and MB840481, respectively.